Application of acid activated natural clays for improving quality of Niger (Guizotia abyssinica Cass) oil. Issue 4 (April 2022) - Yassin, Jemal Mohammed; Shiferaw, Yoseph; Tedla, Abebe
Abstract: Natural clay has been considered as one of the most appropriate, locally available, effective, and low-cost edible oil adsorptive purifying materials. The removal of impurities and colored substances from edible oil increases the quality of oils. This study reports the application of acid activated different clays for bleaching of Niger oil. The clay samples were collected from different parts of North Shoa Zone, Ethiopia namely Zemero, Seladengay and Mehal Meda, and treated by three different acid concentrations (15 %, 20 % and 25 %) with HCl, HNO3, and H2 SO4 . The acid activation boosts the behavior of the clays by manipulating its physical and chemical properties, which highly responsible for the removal of impurities. The characteristic of the clay samples were characterized by using X-ray diffraction (XRD), X-ray Fluorescence spectrometry (XRF), Fourier transform infrared (FTIR) and UV-vis spectrophotometer, respectively. The Niger oil (Guizotia abyssinica Cass) was treated with each activated clays to evaluate for their use as local adsorptive materials. The results indicated that all the clay samples activated with H2 SO4 demonstrated the highest bleaching efficiency compared to the clays activated with HCl and HNO3 under similar conditions. Therefore, 25 % sulfuric acid activated Zemero clay is the most efficient (94.5 %) with adsorbent dose (1 g), contact time (30 min), and temperature (90 °C) compared to Seladengay and Mehal Meda clay samples. The results indicate the adsorption capacities of all the three activated clays and their potential applications for efficient treatment and purification of oils to improve flavor, taste, and shelf life of oil products. Abstract : Color; adsorption; Natural Clays; Edible Oil; Acid Activation.